Nintedanib treatment for pulmonary fibrosis after coronavirus disease 2019 - Hiroaki Ogata; Taisuke Nakagawa; Soichiro Sakoda; Akiko Ishimatsu; Kazuhito Taguchi; Masako Kadowaki; Atsushi Moriwaki; Makoto Yoshida (Respirology Case Reports, 2021)
Abstract A 78‐year‐old Japanese woman with no smoking history suffered from near‐fatal coronavirus disease 2019 (COVID‐19) requiring four‐week invasive mechanical ventilation, with subsequent radiological features of pulmonary fibrosis. Although methylprednisolone gradually improved her respiratory condition, her oxygenation and exercise tolerance had drastically deteriorated, necessitating high‐flow nasal cannula oxygen therapy. In parallel with tapering systemic steroid, the patient was treated with nintedanib. Three months later, the patient was able to walk with a walking aid using oxygen at 4 L/min. The present case is an indication that nintedanib might provide a novel therapeutic approach for managing post‐COVID‐19 fibrosis, although further studies are warranted.